Development and optimization of a new MALDI-TOF protocol for identification of the Sporothrix species complex - Oliveira, M. M. E. (2015)
Accurate species identification of the Sporothrix schenckii complex is essential, since identification based only on phenotypic characteristics is often inconclusive due to phenotypic variability within the species. We used matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) for species identification of 70 environmental and clinical isolates of the Sporothrix complex. A reference database was established for MALDI-TOF MS-based species identification according to minor adjustments in the manufacturer's guidelines. The MALDI-TOF MS clearly distinguished strains of Sporothrix brasiliensis, Sporothrix globosa, Sporothrix mexicana, S. schenckii, Sporothrix luriei and Sporothrix pallida, enabling identification of all isolates at the species level, as confirmed by partial calmodulin gene sequence analyses. The present methodology is simple, reliable, rapid and highly suitable for routine identification in clinical mycology laboratories and culture collections, particularly for updating and reclassifying of deposited Sporothrix isolates.